2017
DOI: 10.1590/abd1806-4841.20175700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment response to autologous transplantation of noncultured melanocyte/keratinocyte cell suspension in patients with stable vitiligo

Abstract: BackgroundVitiligo is a chronic disease characterized by the appearance of achromic macules caused by melanocyte destruction. Surgical treatments with melanocyte transplantation can be used for stable vitiligo cases. ObjectivesTo evaluate treatment response to the autologous transplantation of noncultured epidermal cell suspension in patients with stable vitiligo.MethodsCase series study in patients with stable vitiligo submitted to noncultured epidermal cell suspension transplantation and evaluated at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Similarly, lesions over the joints including elbows, knees and ankles tend to respond less favorably with <30% of the lesions showing excellent repigmentation. 5 , 7 , 26 , 28 30 , 43 Lesions over the joints showed a significantly lower response compared with presternal lesions and those on the trunk and extremities. 6 On the contrary, some authors reported an excellent response of lesions overlying joints with ≥95% repigmentation achieved in 54% of lesions in one study 4 and in 100% of lesions in others.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Similarly, lesions over the joints including elbows, knees and ankles tend to respond less favorably with <30% of the lesions showing excellent repigmentation. 5 , 7 , 26 , 28 30 , 43 Lesions over the joints showed a significantly lower response compared with presternal lesions and those on the trunk and extremities. 6 On the contrary, some authors reported an excellent response of lesions overlying joints with ≥95% repigmentation achieved in 54% of lesions in one study 4 and in 100% of lesions in others.…”
Section: Introductionmentioning
confidence: 91%
“…SV cases showed a significantly better response than NSV with 85% vs 70% repigmentation ( P =0.011) in one study 6 and >50% repigmentation in 88% vs 71% of cases in another study ( P =0.007). 40 Other studies reported a better response in SV cases, although statistical analysis was not performed 2 , 3 , 8 , 26 , 28 , 43 or was not significant. 13 , 38 Immunological disturbances probably interfere with the outcome of transplantation in GV.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations